The relationship between group attachment and career adaptability of college students: a moderated mediation model - Wang, Huiyan; Lu, Feng; Liu, Shaoying (Frontiers in Psychology, 2025)
IntroductionThis study explored the connection between group attachment and career adaptability among college students, considering attachment theory and career construction theory. It also looked into the mediating role of perceived social support and the moderating role of academic achievement level.MethodsThe Career Adapt-Abilities Scale - China Form, The Group Attachment Scale, The Perceived Social Support Scale, and The Academic Achievement Level Questionnaire were used to survey 533 Chinese college students.ResultsThe survey results indicated that perceived social support partially mediated the relationship between group attachment and college students’ career adaptability. The relationship between perceived social support and career adaptability was significantly positively moderated by academic achievement level.DiscussionThe study results improve the understanding of the factors affecting career adaptability and provide evidence for higher education institutions to enhance class group dynamics and boost college students’ employability.